Induktivisme sebagai Basis Pengembangan Ilmu Pengetahuan dalam Islam - Masdar Hilmy (Universitas Islam Negeri Mataram, 2013)
This paper analyses how inductive paradigm has been misperceived and mistreated by Muslims, and discusses the extent to which the inductive paradigm and the deductive one has long been competing to one another throughout the development of science in Islam. This paper argues that the backwardness of Muslim civilization is due to the fact that the inductive paradigm has long been neglected and has been misperceived by Muslim scientists as a Western type entity which should be deconstructed and, therefore, should be put aside. This attitude stems from the Muslims’ attitude towards the Qur’an and Hadith as direct sources of modern science, scientific corpuses from which modern theories of sciences emanate. In order to achieve an advancement of science, Muslims do not have any choice other than treating the inductive paradigm properly as an epistemological as well as methodological apparatus in developing sciences either natural sciences, social humanities and religious as well as Islamic studies.